Compound fractures of the hand metacarpals and phalanges treated by using mini-external fixator - Aboud, Amer G.; Al- Iedani, Mohammed S.; Abdul Razzak, Hazim; Al-Assadi, Tarek K. (AL-Kindy College Medical Journal, 2015)
Background: A review of articles of method in treating compound phalangeal fractures by using mini-external fixator, elaborating the anatomy, mechanics, modalities of treatment, and complications of these types of fractures. Also, it compares between different studies regarding the functional results and final outcome. External fixation of phalangeal fractures is a good method for osteo synthesis in certain situations. The simplicity of the surgical procedure and the minimal disruption of the normal bone architecture also make it appealing.Objectives: Evaluating the functional results of the use of mini-external fixator for the treatment of compound fractures of phalangeal bones of the hand.Method: Our study consists of 15 patients, 12 were male and 3 was female, treated with external fixator for sever open hand fractures at Al-Kindy teaching hospital during the period from June 2011 – June 2013, using 2 K-wires bonded by IV needle cover, or 2 K-wires bonded by bone cement.Results: In comparison between different studies, external fixation offers several advantages. It allows preservation of the bone architecture, union of the fracture, facilitatinghealing of the disrupted area, and good functional results. External fixation is versatile, adapting to a wide range of clinical situations. This method of fixation provides good stability and adequate control of comminuted fractures, allowing not only anatomic restoration but also early active motion.Conclusion: External fixators are appropriate in cases of open, comminuted, unstable fractures. Other appropriate settings for external fixation include temporal management of fractures and length preservation of a functional digit